ANALYSIS OF FIGURATIVE LANGUAGE IN SONG LYRICS OF ROAR BY KATY PERRY - Siagian, Aprina Wati; Sinaga, Kriswan; Natio S. Pane, Debora Ombun (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
This research aimed to discover figurative language of song lyrics “Roar” by Katy Perry. The research methodology employed was descriptive qualitative. This involved examining song lyrics to classify various types of figurative language employed within. The data analysis processes consisted of several steps: reviewing song lyrics, searching for instances of figurative language, discerning specific types of figurative language present, categorizing song lyrics accordingly, and producing comprehensive report or conclusion based on the findings. This research centered on finding figurative language presented in Katy Perry’s song, “Roar”, sourced from the website www.azlyrics.com. After conducting analysis of the data, it became evident that Katy Perry’s song “Roar” was rich in figurative language, with seven distinct forms being identified. These included allegory, hyperbole, metaphor, symbol, repetition, simile, and paradox. Among these, allegory emerged as the prevailing form, appearing nine times. Following closely behind was hyperbole, which made its presence known three times. Repetition and simile appeared three times as well. Lastly, metaphor, symbol, and paradox each made a single appearance. In terms of percentage, the occurrence of allegory accounted for 37.5%, while hyperbole stood at 25%, metaphor and symbol at 4.16% each, repetition and simile at 12.5% each, and paradox at 4.16%.